Effect of anti-breast cancer agent, PQ1, on normal tissues - Ding, Ying; Prasain, Keshar; Nguyen, Thi D.T.; Hua, Duy H.; Nguyen, Thu A. (My University, 2012)
Gap junctions are intercellular channels connecting adjacent cells, allowing cells to transport small molecules. The loss of gap junctional intercellular communication (GJIC) is one of the important hallmarks of cancer. Restoration of GJIC is related to the reduction of tumorigenesis and increase in drug sensitivity. Previous reports have shown that PQ1, a quinoline derivative, increases GJIC in T47D breast cancer cells, and subsequently attenuates xenograft breast tumor growth. Combinational treatment of PQ1 and tamoxifen can lower the effective dose of tamoxifen in cancer cells. In this study, the effects of PQ1 were examined in normal C57BL/6J mice, evaluating the distribution, toxicity, and adverse effects. The distribution of PQ1 was quantified by high-performance liquid chromatography and mass spectrometry. The expressions of survivin, caspase-8, cleaved caspase-3, aryl hydrocarbon receptor (AhR), and gap junction protein, connexin 43 (Cx43), were assessed using western blot analysis. Our results showed that PQ1 was absorbed and distributed to vital organs within 1 h and the level of PQ1 decreased after 24 h. Furthermore, PQ1 increased the expression of survivin, but decreased the expression of caspase-8 and caspase-3 activity. Interestingly, the expression of AhR increased in the presence of PQ1, suggesting that PQ1 may be involved in the AhR-mediated response. Previously, PQ1 caused an increase in Cx43 expression in breast cancer cells; however, PQ1 induced a decrease in Cx43 in normal tissues. Hemotoxylin and eosin staining of the tissues showed no histological change between the treated and the untreated organs. Our studies indicate that the administration of PQ1 by an oral gavage can be achieved with low toxicity to normal vital organs.
The effect of the PQ1 anti-breast cancer agent on normal tissues
Keywords: Adverse effect; Anti-breast cancer agent; Distribution; Gap junction; PQ1; Toxicity